2014
DOI: 10.1002/2013pa002589
|View full text |Cite
|
Sign up to set email alerts
|

Effects of midlatitude westerlies on the paleoproductivity at the Agulhas Bank slope during the penultimate glacial cycle: Evidence from coccolith Sr/Ca ratios

Abstract: Modern primary productivity on the Agulhas Bank, off South Africa, has been proposed to be linked to the midlatitude westerlies. A paleoproductivity record from this area may therefore resolve temporal changes in the westerly dynamics. Accordingly, we produced a coccolith Sr/Ca-based paleoproductivity record from core MD96-2080 (Agulhas Bank slope) during the penultimate glacial-interglacial cycle. Deriving the productivity signal from Sr/Ca requires a correction for a temperature effect, here constrained usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 74 publications
1
15
0
1
Order By: Relevance
“…However, EPP values during these terminations are in similar scale, which are still comparably low (Figure c). This low productivity trend was also observed during T II in the Agulhas Corridor, south of the study area, where an abrupt warm and saline episode during T II did not coincide with a productivity peak [ Mejia et al , ]. A study by Rickaby et al [] shows similar trend in CF Sr/Ca values and suggested the influence of day length and light intensity, in addition to insolation in coccolithophore productivity (Figure b).…”
Section: Discussionsupporting
confidence: 69%
See 3 more Smart Citations
“…However, EPP values during these terminations are in similar scale, which are still comparably low (Figure c). This low productivity trend was also observed during T II in the Agulhas Corridor, south of the study area, where an abrupt warm and saline episode during T II did not coincide with a productivity peak [ Mejia et al , ]. A study by Rickaby et al [] shows similar trend in CF Sr/Ca values and suggested the influence of day length and light intensity, in addition to insolation in coccolithophore productivity (Figure b).…”
Section: Discussionsupporting
confidence: 69%
“…For this study, we used the raw Sr/Ca ratios to measure coccolithophore productivity because a study by Rippert et al [] suggested that the temperature difference in the tropical IO from the Last Glacial Maximum to the Holocene is ~2 to 4°C in maximum. Moreover, temperature‐corrected and raw Sr/Ca data attributed to productivity from the Agulhas Bank showed similar variations, which indicated only a small contribution of temperature to the Sr/Ca record [ Mejia et al , ]. We also calculated the relative carbonate contribution of the individual species to the total assemblage by multiplying the coccolith concentration (species CC/g of sed.)…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Consequently, in a comparable way to the LGM, the increased sea ice during the late Holocene (Fig. 5g), may have displaced the westerlies equatorward, increasing winter wind strength and the length of the dry season at Mfabeni, leading to a decreased influence of the moisture bearing tropical easterlies (Mejía et al, 2014;Toggweiler et al, 2006;Williams and Bryan, 2006). Furthermore, although the westerlies may have had a more northerly position during this time, simultaneous high local summer insolation and warm SSTs (causing strong convective rainfall during summer; Fig.…”
Section: Climate Driving Mechanismsmentioning
confidence: 99%